Teachers in Film: Always in Process - Ahn, Claire; Leggo, Carl (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
Teachers are often portrayed in Hollywood films as superhuman. While these types of films may perpetuate certain stereotypes of teachers, they can also have a great influence. Based on their own teaching experiences, and having viewed and re-viewed the films Dangerous Minds (Bruckheimer, Simpson, & Smith, 1995) and The English Teacher (Despres, LeClair, Salerno, & Zisk, 2013), the authors reflect on the importance of offering pre-service teachers the chance to consider how Hollywood-teacher films can affect their emerging teacher identities. This article is the result of a research project that included an extensive review of 25 Hollywood-teacher films, and through the processes of narrative inquiry provides a self-reflexive discussion on how certain films have shaped the authors’ teaching and teacher identities.